Improving the Soil Properties by Adding Rice Husk Ash (RHA) and Ordinary Portland Cement (OPC): An Experimental Analysis - , Christopher Ehizemhen Igibah; , Olugbenga Oludolapo Amu; , Lucia Omolayo Agashua; , Ernest Tochukwu Ugochukwu (Archives of Current Research International, 2022)
The stabilization capability of rice husk ash (RHA) and Ordinary Portland cement (OPC) was scrutinized using laboratory scrutiny. Three soils (Soil A, B, and C) were improved with various percentages (via weight of dry soil) at 0, 2, 4, 6, 8, and 10% for all stabilizing agents and compacted via BSL (British Standard light) energy. Their impacts were assessed on the strength physiognomies such as UCS (unconfined compressive strength), OMC (optimum moisture content), California bearing ratio (CBR), and MDD (maximum dry density tests based on ASTM (American Standard Testing Materials) codes. The result reveals the optimum values for three lateritic samples, A, B, and C, illustrated a reduction in plasticity for rice husk ash (RSA) stabilizer from 17.32%, 12.67%, and 19.07% (at 6% cement) to 16.32%, 9.90% and 17.00% (at 6% cement and 6% RHA) respectively. Likewise, the optimum Triaxial test result for RHA at 6% with a specified cement content of 6% are A (Deviation stress 595.45KN/m2, Cohesion 10KN/m2, Angle of internal friction 280, and Shear stress 175.5KN/m2), B (Deviation stress 514.75KN/m2, Cohesion 9KN/m2, Angle of internal friction 280 and Shear stress 168.5KN/m2), and C (Deviation stress 530.58KN/m2, Cohesion 10KN/m2, Angle of internal friction 290 and Shear stress 162.0KN/m2.